Salidroside ameliorates cerebral ischemic injury and regulates the glutamate metabolism pathway in astrocytes - Zheng, Xiaoyu; Zhang, Hongwei; Zhang, Yehao; Ding, Zhao; Huang, Zishan; Li, Haoran; Yao, Mingjiang; Song, Wenting; Liu, Jianxun (Frontiers in Pharmacology, 2024)
Background and Aim: Salidroside (SA) is the main active component of Rhodiola rosea L., with potential in treating cardiovascular and cerebrovascular diseases, and cerebral ischemia. However, its efficacy and mechanism in cerebral ischemia remain unclear, particularly its effect on glutamate metabolism. In this paper, we aimed to investigate SA's efficacy in treating cerebral ischemia and its pharmacological mechanism.Experimental procedure: We studied SA's effects on SD rats with cerebral ischemia, evaluating neurobehavior, cerebral water content, infarct size, and brain microstructure. We also assessed its impact on GFAP, GS, and GLT-1 proteins using immunohistochemistry and Western Blot. Additionally, we used SVGp12 cells to simulate cerebral ischemia and measured Glu levels, and used Western blot to observe the level of GS and GLT-1.Results: SA improved neural function, reduced infarct size, and regulated GSH and Glu levels in rats. In cell experiments, SA increased cell viability and decreased Glu concentration after ischemia induction. It also adjusted the expression of GFAP, GS, and GLT-1.Conclusion: SA alleviates cerebral ischemia-induced injury by acting on astrocytes, possibly through regulating the glutamate metabolism pathway.